Early‐pregnancy events and subsequent antenatal, delivery and neonatal outcomes: prospective cohort study. (4th October 2019) - Al‐Memar, M.; Vaulet, T.; Fourie, H.; Nikolic, G.; Bobdiwala, S.; Saso, S.; Farren, J.; Pipi, M.; Van Calster, B.; de Moor, B.; Stalder, C.; Bennett, P.; et al.
ABSTRACT: Objective: To assess prospectively the association between pelvic pain, vaginal bleeding, and nausea and vomiting occurring in the first trimester of pregnancy and the incidence of later adverse pregnancy outcomes. Methods: This was a prospective observational cohort study of consecutive women with confirmed intrauterine singleton pregnancy between 5 and 14 weeks' gestation recruited at Queen Charlotte's & Chelsea Hospital, London, UK, from March 2014 to March 2016. Serial ultrasound scans were performed in the first trimester. Participants completed validated symptom scores for vaginal bleeding, pelvic pain, and nausea and vomiting. The key symptom of interest was any pelvic pain and/or vaginal bleeding during the first trimester. Pregnancies were followed up until the final outcome was known. Antenatal, delivery and neonatal outcomes were obtained from hospital records. Logistic regression analysis was used to assess the association between first‐trimester symptoms and pregnancy complications by calculating adjusted odds ratios (aOR) with correction for maternal age. Results: Of 1003 women recruited, 847 pregnancies were included in the final analysis following exclusion of cases due to first‐trimester miscarriage ( n = 99), termination of pregnancy ( n = 20), loss to follow‐up ( n = 32) or withdrawal from the study ( n = 5). Adverse antenatal complications were observed in 166/645 (26%) women with pelvic pain and/or vaginal bleeding in the first trimester (aOR = 1.79; 95% CI, 1.17–2.76) and in 30/181 (17%) women with no symptoms. Neonatal complications were observed in 66/634 (10%) women with and 11/176 (6%) without pelvic pain and/or vaginal bleeding (aOR = 1.73; 95% CI, 0.89–3.36). Delivery complications were observed in 402/615 (65%) women with and 110/174 (63%) without pelvic pain and/or vaginal bleeding during the first trimester (aOR = 1.16; 95% CI, 0.81–1.65). For 18 of 20 individual antenatal complications evaluated, incidence was higher among women with pelvic pain and/or vaginal bleeding, despite the overall incidences being low. Nausea and vomiting in pregnancy showed little association with adverse pregnancy outcomes. Conclusions: Our study suggests that there is an increased incidence of antenatal complications in women experiencing pelvic pain and/or vaginal bleeding in the first trimester. This should be considered when advising women attending early‐pregnancy units. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.